Implikasi Profesi Wali Santri Terhadap Aktualisasi Perilaku Islami pada Santri Taman Pendidikan Alqurān di Kota Banda Aceh - Lina Fitriany (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Every parent has a dual role in the family between the task of educating and earning a living, so it is feared that parents are less than optimal in carrying out both roles. As the majority of students in the Alqurān Education Park (TPA) have not properly actualized Islamic behavior. Research objectives: 1) To describe the Islamic behavior of students in the TPA Banda Aceh City, 2) To determine the implications of the profession of the santri guardian on the Islamic behavior of students in the TPA Banda Aceh. The qualitative research is descriptive with data sources of students, guardians of students and religious teachers. Data collection techniques through observation, interviews, questionnaires and documentation. Analysis of the interview data with source triangulation and percentage formula for questionnaire data. The results showed: 1) Description of Islamic behavior of students in TPA in the form of worshiping respect for their parents, respecting religious teachers, respecting friends, discipline, maintaining cleanliness, maintaining manners of speech, eating/drinking manners and learning the Alqurān. 2) The professional implications for the Islamic behavior of students at the TPA are related to the working hours of the santri guardians, showing that the majority of santri guardians are civil servants and non-civil servants who have time to educate children's Islamic behavior. Professional implications related to differences in formal education levels taken by civil servant and non-civil santri guardians show that the higher the education of the santri guardian, the better the efforts to educate children's Islamic behavior in the family environment.